My darling husband eaudiobook - Belle, Kimberly (2021)
"Riveting suspense, truly surprising revelations, and silky smooth writing make this one unmissable!" — Joshilyn Jackson, New York Times bestselling author of Mother May I Bestselling author of DEAR WIFE and THE MARRIAGE LIE, Kimberly Belle returns with her most heart-pounding thriller to date, as a masked home invader reveals the cracks in a marriage. Everyone is about to know what her husband isn't telling her... Jade and Cam Lasky are by all accounts a happily married couple with two adorable kids, a spacious home and a rapidly growing restaurant business. But their world is tipped upside down when Jade is confronted by a masked home invader. As Cam scrambles to gather the ransom money, Jade starts to wonder if they're as financially secure as their lifestyle suggests, and what other secrets her husband is keeping from her. Cam may be a good father, a celebrity chef and a darling husband, but there's another side he's kept hidden from Jade that has put their family in danger. Unbeknownst to Cam and Jade, the home invader has been watching them and is about to turn their family secrets into a public scandal. With riveting twists and a breakneck pace, My Darling Husband is an utterly compelling thriller that once again showcases Kimberly Belle's exceptional talent for domestic suspense. Don't miss bestselling author Kimberly Belle's next deeply addictive thriller, The Personal Assistant—where she explores the dark side of the digital world when a mommy-blogger's assistant goes missing! Look for these other pulse-pounding thrillers by Kimberly Belle: The Marriage Lie The Last Breath Stranger in the Lake Three Days Missing Dear Wife The Ones We Trust